Modeling of the supported ionic liquid phase (SILP) catalysis: Improved understanding for reaction optimisation - Buchele, Alexander; Arlt, Wolfgang (19th International Congress of Chemical and Process Engineering, CHISA 2010 and 7th European Congress of Chemical Engineering, ECCE-7, 2010)
Supported ionic liquid phase catalyst systems were applied in continuous gas phase reactions using homogeneous catalysts in fixed bed reactors. The homogeneous transition metal complex was immobilized in the thin film of an ionic liquid (IL) dispersed on the high area surface of an inorganic support, thus bridging the gap between homogeneous and heterogeneous catalysis. Such catalyst systems allowed for a very efficient use of IL because of relatively short diffusion distances of reactants compared to conventional homogenous two-phase organic-ionic liquid catalyst systems. Propylene hydrogenation was investigated. The phase equilibria for all compounds were set up to model the reaction directly in the ionic liquid phase. A tailor-made IL should be used on the support. To tailor this property, the a-priori predictive tool COSMO-RS for solubility calculations was applied. This is an abstract of a paper presented at the 7th European Congress of Chemical Engineering-7 and 19th International Congress of Chemical and Process Engineering CHISA (Prague, Czech Republic 8/28/2010-9/1/2010).